Comparative analysis of lateral earth pressure acting on braced excavation wall - Najmudin, Nor Syahirah (IRC, 2016)
Braced excavation walls commonly are used for underground basement excavation or open cut excavation projects in urban areas. During the excavation process, it is essential not only considering the stability issues of the construction building itself, but also the potential serviceability problem of adjacent properties due to excessive wall deflection and ground movement.